2022
DOI: 10.1186/s12917-022-03250-3
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of dietary Laminaria digitata with alginate lyase on plasma metabolites and hepatic lipid, pigment and mineral composition of broilers

Abstract: Background The Laminaria digitata is an abundant macroalga and a sustainable feedstock for poultry nutrition. L. digitata is a good source of essential amino acids, carbohydrates and vitamins, including A, D, E, and K, as well as triacylglycerols and minerals, in particular iron and calcium. However, the few studies available in the literature with broilers document the application of this macroalga as a dietary supplement rather than a feed ingredient. No study has addressed up until now the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 49 publications
5
3
1
Order By: Relevance
“…Therefore, the increase of the sum n -3 PUFA, and particularly of n -3 long-chain PUFA, in the liver of broilers fed U. lactuca , alone or supplemented with exogenous CAZymes, could be explained by de novo lipogenesis through the intake of the precursor 18:3 n -3 in the biosynthetic pathway of n -3 long-chain PUFA [ 41 ]. These findings corroborate those of Costa et al [ 17 ], who also documented an increase in hepatic n -3 fatty acids, as well as a decrease of n -6/ n -3 ratio, with the incorporation of 15% L. digitata , with or without feed enzymes, to broiler diets. Similarly, Costa et al [ 18 ] reported an increase in meat n -3 PUFA, including EPA, DPA and DHA, with the addition of U. lactuca combined with ulvan lyase.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Therefore, the increase of the sum n -3 PUFA, and particularly of n -3 long-chain PUFA, in the liver of broilers fed U. lactuca , alone or supplemented with exogenous CAZymes, could be explained by de novo lipogenesis through the intake of the precursor 18:3 n -3 in the biosynthetic pathway of n -3 long-chain PUFA [ 41 ]. These findings corroborate those of Costa et al [ 17 ], who also documented an increase in hepatic n -3 fatty acids, as well as a decrease of n -6/ n -3 ratio, with the incorporation of 15% L. digitata , with or without feed enzymes, to broiler diets. Similarly, Costa et al [ 18 ] reported an increase in meat n -3 PUFA, including EPA, DPA and DHA, with the addition of U. lactuca combined with ulvan lyase.…”
Section: Discussionsupporting
confidence: 92%
“…AST, ALT and ALP were reduced by U. lactuca , regardless of the CAZyme supplementation. These changes on aminotransferases activity are within the reference values reported for birds using both micro- and macroalga species, Arthrospira platensis [ 14 ] and L. digitata [ 17 ], respectively. GGT levels were higher in broilers fed U. lactuca alone and supplemented with the recombinant ulvan lyase than the control diet, in resemblance to the variations observed previously by some authors [ 14 , 17 ], yet not implying any kind of liver injury or dysfunction.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations